Thermodynamic optimization of global circulation and climate - Bejan, A. (2005)
The constructal law of generation of flow structure is used to predict the main features of global circulation and climate. The flow structure is the atmospheric and oceanic circulation. This feature is modelled as convection loops, and added to the earth model as a heat engine heated by the Sun and cooled by the background. It is shown that the dissipation of the power produced by the earth engine can be maximized by selecting the proper balance between the hot and cold zones of the Earth, and by optimizing the thermal conductance of the circulation loops. The optimized features agree with the main characteristics of global circulation and climate. The robustness of these predictions, and the place of the constructal law as a selfstanding principle in thermodynamics, are discussed.